Influence Product Domestic Regional Bruto (PDRB), Total Population, And Capital Expenditures On Pad (Regional Generated Revenue) (A Case Study In District And Towns In North Sumatera Province) - Raja, Togu Harlen Lbn.; Hasugian, Putra Raja Tunggah (Advances in Social Sciences Research Journal, 2018)
The objective of the research was to find out and to examine the influence of PDRB( Gross Regional Domestic Product), Total Population,and Capital Expenditures on PAD (Regional Generated Revenue), (a case study in districts and towns in North Sumatera Province). The research used causal method with secondary data. The population was 33 district and municipal governments in North Sumatera Province within 5 years (2010-2015) so that there were 198 observations. The samples were taken by using census sampling technique. The data were analyzed by using multiple regression analysis, aided by an SPSS software program. The result of the research showed PDRB( Gross Regional Domestic Product), Total Population, and Capital Expenditures had positive and significant influence onPAD (Regional Generated Revenue)at the Determinance level of 71,3%. Partially, PDRB( Gross Regional Domestic Product), and Capital Expenditure had positive and significant influence on PAD (Regional Generated Revenue),